The clinical significance of cerebrospinal fluid levels of kynurenine pathway metabolites and lactate in severe malaria. - Medana, I; Hien, T; Day, N; Phu, N; Mai, N; Chu'ong, L; Chau, T; Taylor, A; Salahifar, H; Stocker, R; Smythe, G; Turner, G; et al. (2002)
A retrospective study of 261 Vietnamese adults with severe malaria was conducted to determine the relationship between cerebrospinal fluid (CSF) levels of metabolites of the kynurenine pathway, the incidence of neurologic complications, and the disease outcome. Three metabolites were measured: the excitotoxin quinolinic acid (QA); the protective receptor antagonist kynurenic acid (KA); and the proinflammatory mediator picolinic acid (PA). These measurements were related prospectively to CSF lactate levels. QA and PA levels were elevated, compared with those of controls. There was no difference in the levels of KA between these groups. Although >40% of malaria patients had QA CSF concentrations in the micromolar range, there was no association with convulsions or depth of coma. Levels of QA and PA were associated significantly with death, but a multivariate analysis suggested that these elevations were a consequence of impaired renal function. CSF lactate remained an independent and significant predictor of poor outcome.